ANALISIS PENGGUNAAN BAHAAnalisis Penggunaan Bahasa Indonesia Sebagai Bahasa Pemasaran Dalam Bisnis Tiktok ShopSA INDONESIA SEBAGAI BAHASA PEMASARAN DALAM BISNIS TIKTOK SHOP - Ika Zulianti; Mei Fatmawati; Anggraini Wahyu Ningtyas; Nurvita Sari; Indah Wulandari (Academica : Journal of Multidisciplinary Studies, 2022)
The purpose of this research is to see how the use of Indonesian language can increase sales in businesses or businesses that apply marketing strategies through tiktok shop such as accounts @Skintific_id, @Tantelalapunyacerita, @Minisoindonesia, @Oliviafashion, and @ceokedasbeauty. The research method used is descriptive qualitative method. The object of our research is the use of Indonesian as a marketing language in tiktok shop sales accounts. The data collection technique is an interactive technique that consists of four stages, namely the data collection stage, the data reduction stage, the data presentation stage, and the conclusion drawing stage. The result of the research is that the use of Indonesian language is very important in the marketing promotion of tiktok shop accounts. Not only foreign languages are able to attract consumers, Indonesian language greatly affects the number of buyers in online shops, especially in tiktok shops. So the use of Indonesian in marketing is also able to increase the performance of product sales in a business through the promotion of tiktok shop. Keywords: Consumers; Indonesian Language; Marketing Language; Tiktok Shop